Risk factors related to amputation in diabetic foot patients: single center outcomes - Gancho Kostov; Mladen Doykov; Bozhidar Hristov; Georgi Amaliev; Krasimir Kraev; Daniel Doykov; Eduard Tilkiyan; Lyuboslav Dimov; Rosen Dimov (Folia Medica)
Aim: This study aimed at identifying factors that worsen the prognosis of diabetic foot, one of the most common complications seen in patients with diabetes. Materials and patients: The sample included 230 patients treated in the Department of Surgery at Kaspela University Hospital in Plovdiv, Bulgaria, between January 2016 and May 2022. Of them, 55.65% were men, and 44.35% were women. The age of the patients ranged from 18 to 77 years, with a mean age of 44.4±14.7 years. Results: Diabetic foot patients of grade ≥4 were 1.8 times more likely to be amputated than the rest of the patients (AOR=1.6; 95% CI: 1.504, 4.683). The utilization of inappropriate antibiotics was associated with a 9.47-fold increased risk of amputation (p<0.001). Subsequently, type 2 DM was found to have a 3.63-fold higher risk (p=0.002), poor glycemic control posed a 3-fold increased risk (p<0.001), a body mass index (BMI) greater than 29.5 was linked to a 2.66-fold raised risk (p=0.011), neuropathy was associated with a 2-fold increased risk (p=0.017), and alcohol consumption was linked to a 1.96-fold higher risk (p=0.024). Conclusion: Our results contribute to clinical practice by identifying risk factors that should be considered in the early monitoring and education of patients with diabetes who are at risk for developing diabetic foot. To minimize the risk of developing diabetic foot ulcers, it is critical to optimize antibiotic therapy and prioritize the advantages of adopting a healthy lifestyle, which includes making informed dietary choices, weight management for reducing hyperglycemia, and refraining from harmful behaviors such as alcohol consumption.